Misogyny Portrayed In Christina Dalcher’s Vox - Maharani, Utary; Andayani, Ambar; Jupriono, D. (International Journal of Educational Research & Social Sciences, 2024)
Misogyny is described as hatred of or prejudice against women. It comes together as the cause and effect, part of the cycle with Patriarchy and feminism. The research focuses to find the cause of misogyny and show the portrayal of misogyny reflected by the male character in Christina Dalcher’s Vox. This study is also aimed to explain the effect of misogyny toward Jean McClellan’s life as the main female character in the novel. The writer uses the aspect of misogyny by Kate Manne which discusses two aspects of misogyny, overt, and violent to describe more on the portrayal of misogyny in the analysis. This study uses qualitative research as the method of the study. The results show that there are two causes that arise misogyny through the novel such as women’s character achievement, and pure movement. The misogynist shows the discrimination, harassment, and social judgment toward Jean in workplaces and society in the story. It affects Jean’s life, makes her life in terrified feeling, and constantly losing confidence in herself.